The role of metaphors in the formation of Ukrainian criminalistic terminology (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article investigates the metaphor as a factor in the creation of criminalistic term, it appears the role of metaphors in the formation of Ukrainian criminalistic terminology.
Keywords: metaphor; Ukrainian criminalistic terminology; secondary nomination; common lexicon